(2x +3)(2x +1)− (2x + 5)(2x +7) = (2x+1)(2x+7)−( 6 x² + 9 x − 9)

Question

(2x +3)(2x +1)− (2x + 5)(2x +7) = (2x+1)(2x+7)−( 6 x² + 9 x − 9)

in progress 0
Valentina 2 tháng 2021-10-21T03:19:13+00:00 2 Answers 6 views 0

Answers ( )

    0
    2021-10-21T03:20:15+00:00

    Đáp án:

     

    Giải thích các bước giải:

    mình làm phần bạn bảo sửa lại đề nhé

    (2x +3)(2x +1)− (2x + 5)(2x +1) = (2x+1)(2x+7)−( 6 x² + 9 x − 9)

    ⇔ 4x² + 6x + 2x + 3 – ( 4x² + 10x + 2x + 5) = 4x² + 2x + 14x + 7 – 6x² – 9x +9

    ⇔ 4x² + 6x + 2x + 3 –  4x² – 10x – 2x – 5-  4x² –  2x – 14x -7 + 6x² + 9x – 9 =0

    ⇔ 2x² -11x -18=0

    ⇔ x=  $\frac{ 11 + √265}{4}$       hoăc x =$\frac{11 -√ 266}{4}$ 

    .

    .

                           cho mình câu tl hay nhất nha

    0
    2021-10-21T03:21:04+00:00

    Đáp án+Giải thích các bước giải:

    `(2x+3)(2x+1)-(2x+5)(2x+7)=(2x+1)(2x+7)-(6x^2+9x-9)`

    `<=>4x^2+8x+3-(4x^2+24x+35)=4x^2+16x+7-6x^2-9x+9`

    `<=>-16x-32=-2x^2+7x+16`

    `<=>2x^2-23x-48=0`

    `<=>x=(23+-\sqrt{913})/4`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )